A Lyapunov-Function-Based Control Strategy for Distributed Generations in Hybrid AC/DC Microgrids - Seyedalipour, Sajjad; Bayhan, Sertac; Komurcugil, Hasan (IEEE, 2019)
Microgrids are being emerged increasingly in distributed generation (DG) systems. Instabilities because of dynamic interactions among the power electronic converters available in such systems can be observed. It has been demonstrated that a hybrid network containing a number of power converters can be instable, even though each separate one is stable inherently. Hence, in this paper, a control strategy for parallel voltage-source converters (VSCs) in a hybrid ac/dc microgrid is presented. The proposed strategy is based on Lyapunov function and can guarantee the global asymptotic stability of the whole system simultaneously. The proposed control strategy can be applied to any other multistage converter system. Computer simulations are provided to confirm the analytical results.
28th IEEE International Symposium on Industrial Electronics (IEEE-ISIE) -- JUN 12-14, 2019 -- Vancouver, CANADA
Keywords: Distributed generation; voltage-source converter; Lyapunov function; stability